FACULTY AWARENESS AND USE OF LIBRARY INFORMATION PRODUCTS AND SERVICES IN NIGERIAN UNIVERSITIES - S.O., Popoola (Malaysian Journal of Library and Information Science, 2017)
This paper discusses faculty awareness and use of library information products and services in South-West Nigeria universities. Systematic random sampling method was used to select 446 faculty members from a population of 4,459 in the universities. A questionnaire formed the major instrument for data gathering. The response rate achieved was 89.7 percent and the reliability coefficient of the questionnaire used was 0.72. The study found that there was a significant difference in faculty awareness of available library information products and services. In addition, they did not have sufficient knowledge of those library products and services pertinent to their teaching and research activities. The survey also revealed that the level of knowledge of faculty staff had positive relationship with the frequency of use, consultation with the librarians, faculty status and membership of library related committees. User education programmes coupled with planned public relations were recommended to improve faculty awareness of library information products and services.